Model systems of human immunodef iciency virus (HIV-1) for in vitro eff icacy assessment of candidate vaccines and drugs against HIV-1 - N. B. Rudometova; D. N. Shcherbakov; A. P. Rudometov; A. A. Ilyichev; L. I. Karpenko (Вавиловский журнал генетики и селекции)
HIV infection still remains a major challenge for healthcare systems of the world. There are several aspects on counteracting the HIV/AIDS epidemic. The f irst aspect covers preventive measures including educational campaigns on HIV/AIDS and promotion of a healthy lifestyle, protected sex, and pre-exposure prophylaxis of vulnerable groups. The second aspect is timely HIV testing and the use of antiretroviral therapy when test results come back positive. The third aspect is the scientif ic research associated with discovering new pharmaceutical agents and developing HIV-1 vaccines. Selecting an adequate tool for quick and accurate in vitro eff icacy assessment is the key aspect for eff icacy assessment of vaccines and chemotherapy drugs. The classical method of virology, which makes it possible to evaluate the neutralizing activity of the sera of animals immunized with experimental vaccines and the eff icacy of chemotherapy agents is the method of neutralization using viral isolates and infectious molecular clones, i. e. infectious viral particles obtained via cell transfection with a plasmid vector including the full-length HIV-1 genome coding structural, regulatory, and accessory proteins of the virus required for the cultivation of replication-competent viral particles in cell culture. However, neutralization assessment using viral isolates and infectious molecular clones is demanding in terms of time, effort, and biosafety measures. An alternative eliminating these disadvantages and allowing for rapid screening is the use of pseudoviruses, which are recombinant viral particles, for the analysis of neutralizing activity. Pseudotyped viruses have defective genomes restricting their replication to a single cycle, which renders them harmless compared to infectious viruses. The present review focuses on describing viral model systems for in vitro eff icacy assessment of vaccines and drugs against HIV-1, which include primary HIV-1 isolates, laboratoryadapted strains, infectious molecular clones, and env-pseudoviruses. A brief comparison of the listed models is presented. The HIV-1 env-pseudoviruses approach is described in more detail.